Effects of gelam honey on oxidative stress in lung cancer cells - Goon Jo Aan,; Gunasekaran G,; Muhamad Fitri Ca,; Chandrashegkar S,; Hajar Amalnina Ab,; Raishan S,; Nurul Faiznani Z,; Ismail Nas,; Mohd Yusof Ya, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Gelam honey was reported to exhibit anti-oxidative, anti-tumour and anti-inflammatory properties against many types of cancer. The main aim of the present study was to evaluate the effect of Gelam honey on the oxidative stress level of human lung cancer cells. IC50 of Gelam honey was identified by treating A549 cells with different doses of honey (50-200 mg/ml). The cells were divided into four groups and induced with stress using hydrogen peroxide (H2O2) accordingly: control, H2O2, Gelam honey, H2O2 + Gelam honey. After 24 hrs of treatment, oxidative stress markers such as malondialdehyde (MDA) and protein carbonyl, were determined. Induction of oxidative stress significantly increased the levels of MDA (p<0.05) but had no effect on protein carbonyl levels. Treatment with Gelam honey was found to reduce MDA levels (p<0.05) in A549 cells exposed to H2O2 but had no effect on the level of protein carbonyl. Interestingly, Gelam honey treatment alone had no effects on the levels of MDA and protein carbonyl. In conclusion, Gelam honey reduces lipid peroxidation but not protein oxidation in human lung cancer cells subjected to oxidative stress.